2022
DOI: 10.3390/medicina58030389
|View full text |Cite
|
Sign up to set email alerts
|

Malunion of the Tibia: A Systematic Review

Abstract: Background and Objectives: Tibial malunions are defined as tibial fractures that have healed in a clinically unacceptable position, resulting in deformity such as shortening, lengthening, abnormal rotation, or angulation. These deformities can have adverse effects on patients, such as pain and gait disturbance, as well as long term development of post-traumatic arthritis. This paper seeks to highlight some of the options for surgical management of malunions and detail the strategies and approaches used to mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(228 reference statements)
0
5
0
3
Order By: Relevance
“…The acceptable range of fracture reduction alignment is generally evaluated by length, angulation, and rotation [ 8 , 9 ]. For a tibia fracture, 10–20 mm shortening, 5–10° angulation, and 10–20° rotation are considered to be acceptable [ 10 ]. Tibial malunion occurs in 3–50% of conservative treatment and up to 20% of surgical fixation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptable range of fracture reduction alignment is generally evaluated by length, angulation, and rotation [ 8 , 9 ]. For a tibia fracture, 10–20 mm shortening, 5–10° angulation, and 10–20° rotation are considered to be acceptable [ 10 ]. Tibial malunion occurs in 3–50% of conservative treatment and up to 20% of surgical fixation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…For a tibia fracture, 10–20 mm shortening, 5–10° angulation, and 10–20° rotation are considered to be acceptable [ 10 ]. Tibial malunion occurs in 3–50% of conservative treatment and up to 20% of surgical fixation [ 10 ]. Although plate osteosynthesis has the lowest malunion rate for tibial fractures [ 11 , 12 , 13 ], the malunion rate reaches up to 8.3% even after tibial plating [ 14 ], and midshaft fractures do not have a lower malunion rate than distal fractures [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long bone malunions have a reported incidence of up to 68% with casting/functional bracing and as high as 20% with intramedullary nailing [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although malunions can have variable radiographic and functional outcomes, deformity correction is generally recommended for patients with a high risk of degenerative joint osteoarthritis, a painful deformity, or an unacceptable appearance [ 22 ]. Deformity correction, including leg length discrepancy, can be treated in several different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusive of congenital etiologies, long bone deformities cause pathologic biomechanical forces that can lead to accelerated radiographic and clinical arthritis [ 17 , 18 , 19 , 20 , 21 ]. In general, surgical correction of long bone deformities is recommended in patients with an increased risk of degenerative joint osteoarthritis and for a deformity that causes pain or an unacceptable appearance [ 22 ].…”
Section: Indications For Usementioning
confidence: 99%
“…It can happen after surgery due to poor bone stabilization. Locked intramedullary (IM) and External Fixation are the most popular bone stabilization methods [4,5]. Another study found no difference in 6-and 12-month reoperation rates.…”
Section: Introductionmentioning
confidence: 99%